The Effect of Sales Growth, Company Growth and Company Size on Capital Structure in the Food and Beverages Sub-Sector Listed on the Indonesia Stock Exchange for the 2015-2019 Period: Pengaruh Pertumbuhan Penjualan, Pertumbuhan Perusahaan dan Ukuran Perusahaan Terhadap Struktur Modal Pada Sub Sektor Food and Beverages yang Terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Tofan Dwiyan Rosyadi; Misti Hariasih (Academia Open, 2021)
This study aims to determine the effect of sales growth, company growth and company size on the capital structure. The population used in this study is the food and beverages sub-sector which is listed on the Indonesia Stock Exchange for the 2015-2019 period. This study uses a quantitative method and the object of this research is the population and the sample is selected by the purposive sampling method, namely 6 food and beverages sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The data collection technique uses the company's annual report from the 2015-2019 period. This research was conducted with the help of the Eviews 10 program. The results of this study indicate that the variables of sales growth, company growth and company size simultaneously have a positive and insignificant effect on capital structure. Partially, sales growth has a negative and insignificant effect on capital structure, company growth has a negative and insignificant effect on capital structure and company size has a negative and insignificant effect on capital structure.